2020
DOI: 10.1097/md.0000000000020482
|View full text |Cite
|
Sign up to set email alerts
|

Danggui Sini decoction for treating diabetic peripheral neuropathy

Abstract: Background: Diabetic peripheral neuropathy (DPN) is one of the most common chronic complications of diabetic patients, which seriously affects the quality of life of patients. At present, mainstream drugs have problems such as poor efficacy and side effects. Traditional Chinese medicine (TCM) has extensive clinical experience in the prevention and treatment of diabetes and chronic complications, and it also shows clear advantages in the treatment of DPN. Clinical studies have confirmed that Danggui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Paeoniae Radix Alba is the dried root of Paeonia lactiflora pall, pertaining to Ranunculaceae, which is bitter, sour and slightly cold in nature ( State Pharmacopoeia Commission, 2020 ; Zhang and Ye, 2020 ). Using Western blot, Zhang showed the effect of Paeoniae Radix Alba on TRP in DRG neurons and found that Paeoniae Radix Alba could restore the expression levels of TRPV1 and TRPM8 to normal levels, thus relieving chronic constriction injury of the sciatic nerve ( Zhang, 2020 ).…”
Section: Studies On Regulation Of Transient Receptor Potential Channe...mentioning
confidence: 99%
“…Paeoniae Radix Alba is the dried root of Paeonia lactiflora pall, pertaining to Ranunculaceae, which is bitter, sour and slightly cold in nature ( State Pharmacopoeia Commission, 2020 ; Zhang and Ye, 2020 ). Using Western blot, Zhang showed the effect of Paeoniae Radix Alba on TRP in DRG neurons and found that Paeoniae Radix Alba could restore the expression levels of TRPV1 and TRPM8 to normal levels, thus relieving chronic constriction injury of the sciatic nerve ( Zhang, 2020 ).…”
Section: Studies On Regulation Of Transient Receptor Potential Channe...mentioning
confidence: 99%
“…In recent years, network pharmacology has been widely used to elucidate the mechanism of action of traditional Chinese medicine (TCM) in the treatment of diseases, and to screen the active ingredients and key targets of TCM by constructing a network of compounds and targets. [3,4] As we all know, molecular docking technology plays a key role in drug design, development, and research. By calculating the binding energy of different conformations (small molecules binding to protein receptors), it is convenient to explore potential active compounds for the treatment of diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Chinese medicine believes that a variety of reasons lead to Yin Jin deficiency, blood stasis, Yin damage and inability of Yang Qi or Yang Qi can not reach the end of the limbs, DPN symptoms gradually appear. It was found that Angelica Sini Decoction in "Treatise on Febrile Diseases" can play a role by regulating NF-κb [4] , RhoA/ROCK [5] , Ca 2+ , AGEs-RAGE [6][7][8] and other signaling pathways, or by reducing inflammatory factors [9] and improving the expression levels of TrkA protein [10] . The clinical data of Angelica Sini Decoction in the treatment of DPN were analyzed to provide more ideas for the treatment of DPN.…”
Section: Introductionmentioning
confidence: 99%